2020
DOI: 10.3390/antiox9121239
|View full text |Cite
|
Sign up to set email alerts
|

The Resistance of Drosophila melanogaster to Oxidative, Genotoxic, Proteotoxic, Osmotic Stress, Infection, and Starvation Depends on Age According to the Stress Factor

Abstract: We studied how aging affects the ability of Drosophila melanogaster to tolerate various types of stress factors. Data were obtained on the resistance of D. melanogaster to oxidative and genotoxic (separately paraquat, Fe3+, Cu2+, and Zn2+ ions), proteotoxic (hyperthermia, Cd2+ ions), and osmotic (NaCl) stresses, starvation, and infection with the pathological Beauveria bassiana fungus at different ages. In all cases, we observed a strong negative correlation between age and stress tolerance. The largest change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 114 publications
(137 reference statements)
1
13
0
1
Order By: Relevance
“…This was not the case however, and instead we found that short-term isoleucine deprivation reduced the nicotine resistance of males. Interestingly, fully-fed males were more tolerant to nicotine than fully-fed females, which is surprising given that young females typically have greater resistance to a range of stressors than the same age males (Belyi et al 2020). This could reflect a difference in initial investment capabilities of the sexes, as the females in our experiments were mated and so were committed to a greater reproductive investment than the males.…”
Section: Discussionmentioning
confidence: 96%
“…This was not the case however, and instead we found that short-term isoleucine deprivation reduced the nicotine resistance of males. Interestingly, fully-fed males were more tolerant to nicotine than fully-fed females, which is surprising given that young females typically have greater resistance to a range of stressors than the same age males (Belyi et al 2020). This could reflect a difference in initial investment capabilities of the sexes, as the females in our experiments were mated and so were committed to a greater reproductive investment than the males.…”
Section: Discussionmentioning
confidence: 96%
“…Cells were incubated for 3 days and, at day 3, diluted again to 10 6 cells/ml and treated with a second dose of dsRNAs as for day 0 for 3 more days. To induce hyperosmotic stress, cells were treated with 300mM NaCl for 1 hour, which is in the range previously used for hyperosmotic stress in Drosophila (250mM – 400mM) 35, 36 . Recovery conditions included incubation in the above hypertonic media for 1 hour followed by incubation in isotonic SFX media for 1 hour.…”
Section: Methodsmentioning
confidence: 99%
“…To alter pairing interactions, we took advantage of the fast and reversible response to 3D chromatin organization that, like previously described in mammalian cells 34 , Drosophila cells undergo upon hyperosmotic cellular stress. In Drosophila cells, it was shown that hyperosmotic stress reduces nuclear volume, promotes rapid and reversible chromatin condensation, and induces delocalization of architectural proteins into insulator bodies [35][36][37] . However, how these changes impact 3D chromatin organization is not known.…”
Section: Introductionmentioning
confidence: 99%
“…The activity data were extracted at 1 h bin (Wang et al, 2020 ). Over 100 flies were used for each line (Belyi et al, 2020 ). For details, please see the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%